Dentists' Knowledge and Attitudes towards Teledentistry - Binarti, Irma; Sianita, Pricillia Priska; Yeni, Perischa Husma (Formosa Journal of Applied Sciences, 2024)
Teledentistry is a combination of telecommunications and dentistry involving the exchange of clinical information and images over remote distances for dental and oral consultation and treatment planning. Knowledge and attitude of dentists towards teledentistry are needed as an effort to increase access to dental and oral health care in terms of environmental aspects, awareness, and health management including prevention and treatment, as well as to understand the utilization and challenges that will be faced in patients dental and oral health problems. Objective: To conduct an integrative review of scientific evidence that explains the knowledge and attitude of dentists towards teledentistry. Method: Reviewed of twelve (12) journals from Ebsco, Pubmed, Google Scholar, ResearchGate databases, textbooks, and various other international journals websites, using international keywords knowledge, attitude, dentists, teledentistry.